A Educação Superior pública brasileira: uma análise dos governos de Lula a Bolsonaro - Andréa Araujo do Vale; Savana Diniz Gomes Melo (Revista Trabalho, Política e Sociedade, 2023)
The article aims to problematize the higher education projects of governments from Lula to Bolsonaro with regard to Public Institutions of Higher Education (IPES). It results from qualitative, exploratory analysis and uses bibliographic and documentary research. The study shows that the first governments of the Workers' Party did not materialize the defense of public education as a right, but operated its neoliberal reconfiguration with democratizing nuances. The Temer and Bolsonaro governments promoted an open attack on higher education. The new Lula government points to rearticulate the conversion of IPES to the education project of/for capital, capturing workers in networks of hope and subordination, such as that expressed by the introduction/maintenance of corporate labor management devices.